Bit error rate performance of orthogonal frequency‐division multiplexing relaying systems with high power amplifiers and Doppler effects. Issue 8 (20th April 2011) - Ahmed, Hassan A.; Sulyman, Ahmed Iyanda; Hassanein, Hossam S.
ABSTRACT This paper analyzes the bit error rate performance of orthogonal frequency‐division multiplexing systems in mobile multihop relaying channels. We considered the uplink scenario and quantified the effects of mobile channel impairments such as Doppler shift due to user mobility per hop, high power amplifier distortions when amplifying the transmitted/relayed orthogonal frequency‐division multiplexing symbol per hop, and the cumulative effects of these impairments on multihop relaying channels. It was shown that the resulting intercarrier interference due to the cumulative effects of the phase noise generated by these impairments per hop becomes very significant in a multihop relaying communication system and severely degrades the bit error rate performance of the system. Simulation results agree well with and validate the analysis. Copyright © 2011 John Wiley & Sons, Ltd.